Policy Perspective on Productivity Needs for Livestock Biotechnology in Ethiopia - Kebede, B. (International Service for National Agricultural Research, 2001)
Although the statistics available on the actual size are outdated and inconsistent, there is no doubt that Ethiopia has a huge livestock population. The ruminant livestock population is the largest in Africa and among the top 10 in the world. Livestock accounts for an estimated 16% of the total GDP and about 30% of the agricultural GDP. It plays a key role in the overall farming system, serving as a source of draught power for cultivating an estimated 6 million hectares of crop land annually. It also provides milk, meat, manure, hides and skins as well as a source of cash for the 85% of the population that live in the rural areas.